Green Banking : Realizing Renewable Energy Projects - Böttcher, Jörg (De Gruyter Oldenbourg, 2020)
Green Banking is the first guide encompassing all the disciplines necessary to realize renewable energy projects. This book focuses on cost-competitive and mature technologies, and on the processes enabling to develop, finance and execute such utility-scale projects. The book starts with the aspects relevant for every form of renewable energy. It covers essential themes such as the role of renewables amid a changing energy world, the importance of the regulatory regime, its social acceptance and bankability criteria, to name only a few. Chapters describe project financings vehicles for a range of renewable energy technologies including solar photovoltaic power plants, onshore wind farms and offshore wind farms. The book give readers a unique perspective on how renewable energy projects are realized, and is a go-to reference manual for understanding how the different project stakeholders act. All of the articles are provided by authors with an ample experience in renewable energies and many years experience. This book is especially useful for people working in this industry or students willing to get better knowledge out of their field of experience.